1976
DOI: 10.1073/pnas.73.4.1284
|View full text |Cite
|
Sign up to set email alerts
|

Interferon treatment of mice: enhanced expression of histocompatibility antigens on lymphoid cells.

Abstract: Treatment of young and mature mice with potent mouse, interferon preparations results in a marked enhancement of the expression of histocompatibility antigens on the surface of thymocytes and splenic lymphocytes as measured by an enhanced absorption of alloantiserum. We postulate that such modifications of the cell surface may reilect an effect of interferon on lymphocyte maturation and may be relevant to the effect of interferon on lymphocyte function.Since interferon can affect both the division and function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
47
0
2

Year Published

1979
1979
1999
1999

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 145 publications
(52 citation statements)
references
References 20 publications
3
47
0
2
Order By: Relevance
“…In addition, there is convincing 2CAT (A) or CAT3M-L1(+) (B). Panels C and D: CAT assays evidence that the expression of class I genes can be modubssing the effects of interferon on L-cell lines L-L1(+)2 (C) and lated by exogenous factors like mitogens, immunomodula-1(+)dll (D), stably transfected with CAT3M-Ll(+) and tors, and infectious agents (19,22). Such alterations in the 173M-Ll(+)dl, respectively.…”
mentioning
confidence: 99%
“…In addition, there is convincing 2CAT (A) or CAT3M-L1(+) (B). Panels C and D: CAT assays evidence that the expression of class I genes can be modubssing the effects of interferon on L-cell lines L-L1(+)2 (C) and lated by exogenous factors like mitogens, immunomodula-1(+)dll (D), stably transfected with CAT3M-Ll(+) and tors, and infectious agents (19,22). Such alterations in the 173M-Ll(+)dl, respectively.…”
mentioning
confidence: 99%
“…It can modify the distribution and, thus, the expression of cell membrane antigens (Lindahl et al, 1976), affect the phenotypic expression of cells (Chany & Vignal, 1970), the synthesis of the cytoskeleton (Pfeffer et al, 1980;Bourgeade et al, 1981;Chany, 1981) and decrease cell multiplication (Paucker et al, 1962). Fowler et al (1980) have recently identified an interferon-like substance present in pools of murine placentas, the amount of which increased progressively during gestation.…”
mentioning
confidence: 99%
“…Part of the immune defense strategy against virally infected cells is the production of interferons (IFNs), which have the effect of increasing the level of class I antigens in a wide variety of cell types (6,9,21,27). As a consequence of this augmentation, presentation of foreign antigens to the appropriate immune effector cells may be facilitated.…”
mentioning
confidence: 99%